EFEKTIVITAS VERMICOMPOST SEBAGAI SUMBER NUTRISI ORGANIK PADA TANAMAN SAWI (Brassica juncea L.) DI TANAH ALUVIAL - Maylani Lucky; Daniel Daniel (Innofarm : Jurnal Inovasi Petanian, 2025)
The increasing demand and high commercial value of mustard greens prompted this study to evaluate the effects and determine the optimal dosage of vermicompost on the growth and productivity of mustard greens cultivated in alluvial soils, which are characterized by low fertility and the need for sustainable organic nutrient sources. The experiment was conducted at the Green House Keling Kumang Institute of Technology using a Completely Randomized Design (CRD) with five vermicompost dosage treatments (50, 100, 150, 200, and 250 g/plant) and four replications. Data were analyzed using analysis of variance (ANOVA), followed by the Honestly Significant Difference (HSD) test to identify significant differences among treatments at a 5% significance level. The results showed that vermicompost application significantly affected plant height at 2 to 4 weeks after planting, with the highest average reaching 24.63 cm, as well as leaf number, fresh plant weight, and fresh shoot weight (without roots). The application of 250 g/plant produced the highest values across all parameters, although it was not significantly different from the 200 g/plant dosage. These findings indicate that vermicompost improves soil fertility by stimulating microbial activity, increasing humus content, and releasing natural hormones that support plant growth. Therefore, the application of vermicompost at 250 g/plant is recommended to sustainably enhance the productivity of mustard greens in alluvial soils. Keywords: Alluvial Soil, Growth, Mustard Greens, Vermicompost, Yield.